Pembangunan Hutan Kota Dan Ketersediaan Lahan - Dikson Junus (JURNAL LEGALITAS, 2009)
Town forest in its growth, ahead have been converted to become the farm of agricalture and residence in line with resident growth, growth of centre of activities which is one with the residence have instituted to form an urban region. its his weak is society knowledge, governmental agency and also the straightening of existing law, and on the other hand quickly it him resident growth claim the availibility of farm for the settlement of and effort tending to to push the town growth to development of medium and infrastructure of eye physical, and tend to the green air-gop minimization or town forest as town lung. functioned to displaced more amount town farm become the commerce area, industrial area and settlement area and also prasarana walke and other Keyword: Townforest, open space green, area settlement